Somatic and psychological problems in a cohort of sexually abused boys: a six year follow up case-control study. Issue 3 (1st March 2002) - Price, L; Maddocks, A; Davies, S; Griffiths, L
Abstract : Aims: To obtain information about the health and well being of 108 boys six years after their involvement with the same paedophile. Methods: Case–control study of the health records of 93 male victims of a major episode of school based child sexual abuse and 93 matched controls. Interviews with a sample of their general practitioners. Results: The number and frequency of reported health problems were similar in both cases and controls. However, abused boys were more likely than controls to present with symptoms that persisted for more than a year (31 cases compared with 10 controls). Conclusions: Boys who have previously suffered sexual abuse at school did not utilise primary health care services more than a group of age matched controls. They did not present with psychological or somatic problems different from those presented by non-abused boys. However, abused boys were more likely to complain of persistent somatic or psychological problems lasting more than a year. This pattern appeared to persist after the abuse had stopped and the perpetrator imprisoned.